Enhancement of Sales Competencies in Property Marketing Amidst the New Normal Era - Hendriyanto, Feri; Purwono, Rudi; Madyawati, Sri Pantja; Suhariadi, Fendy (Technium Social Sciences Journal, 2024)
The COVID-19 pandemic significantly impacted various sectors, including the residential property market, which saw a reduction in sales across all housing categories—small, medium, and large (Bank Indonesia, 2020). This study was designed to assess the enhancement of sales competencies in property marketing during the transition to a new normal. Utilizing a qualitative approach with a systematic literature review, the research aimed to address the growing need to elevate the skills of salespersons in this field. Key competencies highlighted as essential included: entrepreneurial spirit; effective, honest, authentic, and integrity-based communication; expert negotiation skills; and versatility in strategy adaptation. Furthermore, the study detailed the comprehensive skill set necessary for property marketing professionals, encompassing the ability to manage consumer grievances; provide guidance on both legal and non-legal aspects of property transactions; demonstrate advanced negotiation capabilities; engage in precise targeting and marketing planning; perform accurate property valuations; deliver outstanding service; and support clients throughout the entire property buying and selling process.